An anomalous relationship of the maxillary artery with the mandibular nerve branches: A rare case report of two anatomical variations - Annette P Occhialini; Manasa S Muppirala; Sidharth Nayak; Christopher T Nguyen; Hoang H Nguyen; Haley L Nation (Wolters Kluwer Medknow Publications, 2023)
The maxillary artery (MA) and mandibular nerve are important structures in the infratemporal fossa (ITF) supplying large portions of the face. During a medical dissection course, two rare anatomical variations pertaining to the MA's relationship to the mandibular nerve branches were found in three ITF. In these cases, the MA was seen to travel medial to the mandibular nerve branches. Case 1 had bilateral, asymmetric variations. On the left, the MA traveled medial to a trunk formed by the inferior alveolar and lingual nerves and lateral to the chorda tympani nerve (CTN). On the right, the MA passed lateral to the lingual and CTNs and medial to the inferior alveolar nerve. Case 2 had a unilateral variation on the left such as the variation seen on the right in Case 1. A clear understanding of MA variations has several clinical implications. This study provides a resource that may prevent complications such as bleeding, hematoma, and injury to the mandibular nerve or its branches during clinical procedures.